Extending the Framework TAO with Norms for Multi-Agent Systems - Freire, Emmanuel S. S.; Cortés, Mariela I.; Gonçalves, Enyo J. T.; Lopes, Yrleyjânder S.; Souza, Leandro L. C. de (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2012)
The increasing complexity of systems poses a challenge to Software Engineering. The existence of Normative Multi-Agent Systems, where the agents’ behavior is governed by norms, promotes the need for an ontology capable of defining these related concepts. In this context, we highlight TAO, a conceptual framework for (representing) MAS, used as a foundation to the MAS-ML modeling language. However, the support for representing of the norm concepts is limit. This paper describes the extending the TAO through of the creation of new abstraction norm and its relationships. Additionally, the structure of some abstractions defined in the previous version was changed because of the inclusion of the norm concepts. Through a case study, we demonstrate the use of the proposed extension to represent the elements of a virtual marketplace.